MMS Observation of Secondary Magnetic Reconnection Beside Ion‐Scale Flux Rope at the Magnetopause. Issue 16 (24th August 2020) - Dong, X.‐C.; Dunlop, M. W.; Wang, T.‐Y.; Trattner, K. J.; Russell, C. T.; Giles, B.
Abstract: Using high‐resolution data from Magnetospheric Multiscale (MMS) mission, we report an in situ observation of a secondary reconnection electron diffusion region (EDR) beside the leading edge of an ion‐scale flux rope at the magnetopause. This reconnection EDR is characterized by strong electron current and electron jet reversal, a normal Hall electric field, unmagnetized electrons with nongyrotropic distributions, a large parallel electric field, and strong energy dissipation. The ion‐scale flux rope beside the EDR consists of a force‐free structure with diameter of only ~3 ion inertial lengths. Our observation of secondary reconnection beside the flux rope gives further evidence that flux ropes can be created and evolved in the reconnection exhaust region. Plain Language Summary: Small‐scale flux transfer events (FTEs), characterized by a helical flux rope structure, play a significant role in the macroscopic and microscopic physical process during magnetic reconnection at the magnetopause. Although they are widely observed at the magnetopause boundary layer, the mechanisms of generation and evolution remain an open question. In this letter, we report in situ observation of a secondary reconnection region beside the leading edge of a small‐scale FTE, and thus, our work could contribute to understanding the relation between flux ropes and magnetic reconnection at the magnetopause. Key Points: First in situ observation of secondary reconnection diffusion region beside ion‐scale flux rope at the magnetopause is reported The observation provides further evidence for the creation and evolution of flux ropes in the reconnection exhaust region